Realizing Armenia's High-Tech Potential - World Bank (World Bank, Washington, DC, 2019)
Armenia's economy is heavily reliant on domestic demand, which is itself driven by remittances that support local construction and consumption. Armenia will need to shift to an export led strategy if it is to move from middle income to high-income status. Because Armenia is a landlocked country with comparatively high trading costs in physical goods, high-tech digital exports will continue to be key to Armenia's growth. This report seeks to identify strategic opportunities for Armenia’s private sector in high-tech global value chains (GVCs) and also highlights reforms that could support Armenia’s evolution. The study builds on the FY18 Armenia Systematic Country Diagnostic, which identifies value-chain development as a core building block for sectoral growth. Although the report is targeted at policy makers in the Armenian government, sectoral development strategies rely heavily on strong private sector engagement and open public-private dialogue. Armenia's tech community may therefore also take interest in this analysis.